Effects of Hydroxychloroquine on Maternal and Fetal Outcomes in Pregnant Patients with Lupus: A Systematic Review and Meta-Analysis - An-Hao Liu; Xiu-Wen Li; Yue-Wen Yu; Bin Xu; Rui Lei; Chong Ren; Xue-Ru Ruan; Li-Li Tian; Yu-Ping Ma; Ming-Zhu Ye; Xiu-Min Huang; Xun Chen (Clinical and Experimental Obstetrics & Gynecology)
Background: The effects of hydroxychloroquine (HCQ) on maternal and fetal outcomes in pregnant patients with systemic lupus erythematosus (SLE) have not been fully elucidated in recent research. This study aimed to provide a more comprehensive evaluation of the efficacy and safety of HCQ in pregnant patients with SLE. Methods: A systematic search of relevant articles was conducted using Medline, Embase, Scopus, Web of Science, and the Cochrane Library from inception to October 4th, 2023. The risk of bias in the included studies was assessed using the Newcastle-Ottawa Scale or Cochrane's Quality Assessment Form. Data on maternal and fetal outcomes of the HCQ treatment groups (HCQ+) and control groups (HCQ–) were extracted, analyzed and evaluated. Pooled odds ratios (ORs), pooled relative risks (RRs), and weighted mean differences with 95% confidence intervals (95% CIs) were calculated for the meta-analysis using Stata/MP V.18. Results: This meta-analysis included 17 studies, involving a total of 2238 pregnant patients with SLE. Compared to the HCQ– groups, the HCQ+ groups exhibited a significant reduction in the incidence of preeclampsia (RR = 0.51, 95% CI: 0.37–0.71), high lupus activity (RR = 0.77, 95% CI: 0.64–0.92), gestational hypertension (OR = 0.41, 95% CI: 0.18–0.91), premature delivery (RR = 0.71, 95% CI: 0.60–0.84), and fetal growth restriction (OR = 0.61, 95% CI: 0.43–0.85). Additionally, the HCQ+ groups exhibited a significant increase in fetal birth weight of 0.21 kg (95% CI: 0.09–0.33). No significant differences were revealed in the other 15 pregnancy outcomes between the two groups. Conclusions: Despite the presence of a certain heterogeneity among the included studies, this study provides a more comprehensive evaluation of the efficacy and safety of HCQ in pregnant patients with SLE.